P II – 3–8 Benefits of participation citizen science in recovery programs (post-nuclear accidents). (18th March 2018) - Liutsko, Liudmila; Cardis, Elisabeth
Abstract : Background/aim: Nowadays citizen-science are volunteers that are involved in research with purposes of their own benefits for volunteers themselves (education) or for the benefit of the project, sometimes with effects on potential changes in a society. The aim of SHAMISEN SINGS project is to explore more benefits and practical uses for and of such volunteers in post-accidental period after nuclear disasters. Methods: An analytical review of peer-reviewed publications on a topic citizen-science in general and specifically related to radiation, nuclear disasters and dosimetry; as well as main lessons learnt from practical experiences on post-accidental recovery programs after the Chernobyl and Fukushima nuclear accidents (output from the SHAMISEN project – Nuclear Emergency Situations: Improvement of dosimetry, Medical and Health Surveillance). Results: The results of peer reviewed publications show a small proportion (0.02%) related to radiation topic with citizen-science approach: 18 publications were detected by PubMed search with key words 'citizen-science' or 'citizen science' and 'radiation', 5 inputs with 'nuclear disasters' and 2 for 'dosimetry'. After checking the abstracts for their context, it was found the only relevant publication by Brown et al. (2016) concerning to the tool and program 'Safecast: successful citizen-science for radiation measurement and communication after Fukushima'. However, the lessons learnt from the SHAMISEN project highlight the importance of public involvement in the practical post-accidental recovery that make them more sufficient in their daily life to prevent their health and improve well-being. Conclusion: Citizen-science is a useful approach in post-accidental recovery. It can provide information to affected populations – about exposure (dynamics) and health – and can also contribute to the environmental monitoring (complementary to experts), decision-making processes, and, monitoring of health and support of affected publications to take control of their own radiological protection.